Many-body interference in kagome crystals - Chunyu Guo; Kaize Wang; Ling Zhang; Carsten Putzke; Dong Chen; Maarten R. van Delft; Steffen Wiedmann; Fedor F. Balakirev; Ross D. McDonald; Martin Gutierrez-Amigo; Manex Alkorta; Ion Errea; et al. (Nature, 2025)
Abstract When electrons in metals act collectively, they enable emergent phenomena and electronic functionalities that transcend the behaviour of individual particles 1 . Coherent collective charge motion has so far been observed primarily in superconductors, in which it arises with the formation of Cooper pairs 2,3 . Here we report experimental evidence for coherent charge transport in the normal state of the kagome metal CsV 3 Sb 5 , indicative of a distinct collective electronic state. The signature is a set of magnetoresistance oscillations in mesoscopic crystalline pillars under in-plane magnetic fields, with a periodicity determined by the number of magnetic flux quanta h / e threading between adjacent kagome layers—effectively forming an interlayer Aharonov–Bohm interferometer. The cooperative nature of this phenomenon is evidenced by a non-analytic angular dependence characterized by abrupt transitions between discrete oscillation frequencies and its persistence over length scales that exceed the single-particle mean free path. Notably, the oscillation amplitude matches other anomalous electronic responses reported in CsV 3 Sb 5 , pointing to an underlying mechanism that establishes intrinsic coherence. These findings shed new light on the debated nature of correlated order in kagome metals and establish CsV 3 Sb 5 as a platform for realizing long-range coherent charge transport in the absence of superconductivity—opening new directions for coherence in correlated electron systems beyond conventional models.